2007
DOI: 10.1083/jcb.200610022
|View full text |Cite
|
Sign up to set email alerts
|

A CDK-related kinase regulates the length and assembly of flagella in Chlamydomonas

Abstract: Little is known about how cells regulate the size of their organelles. In this study, we find that proper flagellar length control in Chlamydomonas reinhardtii requires the activity of a new member of the cyclin-dependent kinase (CDK) family, which is encoded by the LF2 (long flagella 2) gene. This novel CDK contains all of the important residues that are essential for kinase activity but lacks the cyclin-binding motif PSTAIRE. Analysis of genetic lesions in a series of lf2 mutant alleles and site-directed mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
135
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 61 publications
7
135
0
1
Order By: Relevance
“…Ciliogenesis, cilium length and morphology and the organization of signaling pathways in cilia are regulated (Mukhopadhyay et al, 2008;Quarmby, 2004;Sorokin, 1962;Wang et al, 2006). Although genetic analyses have identified several kinases that modulate cilia length (Bengs et al, 2005;Berman et al, 2003;Burghoorn et al, 2007;Tam et al, 2007), little is known about the molecular mechanisms involved; however, intraflagellar transport (IFT) is a probable process (Blaineau et al, 2007;Dentler, 2005;Engel et al, 2009;Evans et al, 2006;Marshall et al, 2005;Pan and Snell, 2005). IFT is responsible for bi-directional transport of structural and signaling components of the cilia along a microtubular axoneme.…”
Section: Introductionmentioning
confidence: 99%
“…Ciliogenesis, cilium length and morphology and the organization of signaling pathways in cilia are regulated (Mukhopadhyay et al, 2008;Quarmby, 2004;Sorokin, 1962;Wang et al, 2006). Although genetic analyses have identified several kinases that modulate cilia length (Bengs et al, 2005;Berman et al, 2003;Burghoorn et al, 2007;Tam et al, 2007), little is known about the molecular mechanisms involved; however, intraflagellar transport (IFT) is a probable process (Blaineau et al, 2007;Dentler, 2005;Engel et al, 2009;Evans et al, 2006;Marshall et al, 2005;Pan and Snell, 2005). IFT is responsible for bi-directional transport of structural and signaling components of the cilia along a microtubular axoneme.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about how this diversity is achieved. Different types of signaling molecules, including second messengers (Mukhopadhyay et al, 2008;Ou et al, 2009;Besschetnova et al, 2010;Abdul-Majeed et al, 2012), kinases (Berman et al, 2003;Wang et al, 2006;Burghoorn et al, 2007;Tam et al, 2007;Miyoshi et al, 2009;Omori et al, 2010), phosphatases (Kim et al, 2010;ClĂ©ment et al, 2011;Abdul-Majeed et al, 2012) and G proteins (Burghoorn et al, 2010) have been shown to regulate cilia length and cilia morphology. Since these signaling pathways also regulate transport, both in and toward the cilium, it is likely that these transport processes play a role in regulating cilium length and morphology (Silverman and Leroux, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Chlamydomonas, several long flagella mutants have been isolated (McVittie, 1972;Jarvik and Rosenbaum, 1980;Barsel et al, 1988;Asleson and Lefebvre, 1998). Intriguingly, two of them encode kinases, suggesting the involvement of a signaling cascade in regulating cilia length (Berman et al, 2003;Tam et al, 2007). Currently, the underlying mechanism for cilia length control remains elusive.…”
Section: Cilia Biogenesismentioning
confidence: 99%